Effects of lowered dialysate sodium on left ventricle function and brain natriuretic peptide in maintenance of hemodialysis patients. (February 2017) - Akyol, A; Akdag, S; Asker, M; Gumrukcuoglu, HA; Duz, R; Demirel, KC; Ozturk, F; Yaman, M; Sahin, M; Simsek, H; Tuncer, M; Begenik, H
Introduction: Impaired diastolic flow is characterized by decreased left ventricular (LV) filling diastole, abnormal LV distensibility, or delayed relaxation. B-Type natriuretic peptide (BNP) is an indicator of various cardiovascular diseases and body volume status. The aim of this study was to determine whether the lowering of dialysate sodium (Na) levels is effective on LV systolic and diastolic parameters and BNP in the maintenance of hemodialysis patients. Materials and Methods: The study included 49 chronic hemodialysis patients. Left atrium (LA) diameter and LV ejection fraction, LV systolic and diastolic diameter, deceleration time (DT), pulmonary artery pressure (PAP), inferior vena cava diameter (IVCD), early diastolic transmitral flow ( E ) and late diastolic transmitral flow ( A ) velocities, E / A ratio, isovolumic relaxation time, peak early diastolic velocity ( E ′), late diastolic velocity ( A ′) of tissue Doppler mitral annulus, and flow propagation velocity of mitral inflow ( V p ) were measured before and 6 months after hemodialysis with low Na dialysate. Results: Six months after low Na hemodialysis, a decrease was observed in echocardiographic parameters such as PAP and IVCD ( p < 0.05, p < 0.001, and p < 0.001, respectively). However, a significant difference was not observed in LA diameter. In LV diastolic measurement of E and A waves, E / A ratio, DT, V p, septal E ′ and A ′, and lateral E ′ and A ′ exhibited significant improvement by low Na HD. BNP level was significantly reduced ( p < 0.001). Conclusions: Lowered dialysate Na concentration improves PAP, IVCD, and LV diastolic properties assessed by mitral inflow filling, tissue Doppler velocity, and mitral inflow velocity propagation.